Polypharmacy in Pediatric Palliative Care: Exploring Discrepancies Between Physicians and Pharmacists - Daniele Mengato; Anna Zanin; Fernando Baratiri; Lisa Pivato; Laura Camuffo; Franca Benini; Francesca Venturini (Children)
Background/Objectives: Off-label drug use is prevalent in pediatric care, particularly in pediatric palliative care (PPC), due to the scarcity of pediatric-specific formulations and clinical trials. Differences in perception between healthcare professionals regarding off-label prescriptions underscore the complexity of this practice and highlight the need for improved collaboration to optimize therapeutic outcomes. Methods: A cross-sectional observational study was conducted from August to October 2021 at the PPC center of the University Hospital of Padova, Italy. Data were collected from medical records of 169 patients. Off-label prescriptions were independently assessed by two physicians and two clinical pharmacists using respective reference sources. Discrepancies were resolved through consensus. Statistical analyses included the χ2-test for categorical variables and t-tests for continuous data. Results: Among the 993 drug prescriptions analyzed, the pharmacists reported a higher proportion of off-label uses (32.9%) compared to the physicians (18.4%; p < 0.05). After a consensus, 26.5% of the prescriptions were identified as off-label, with 67.9% due to indications, 49.6% due to dosage, and 44.4% due to age discrepancies. Conclusions: This study suggests a high prevalence of off-label prescribing in pediatric palliative care (PPC) and highlights differing professional perspectives, underscoring the potential benefits of exploring standardized protocols and enhanced interdisciplinary collaboration. Enhanced communication between healthcare providers, alongside the development of registries and clinical trials, is essential for improving the safety and efficacy of off-label drug use in pediatric populations. A flexible regulatory framework and customized galenic formulations could further support these goals.